Innovation Barriers and Enablers that Affect Productivity in Uganda Building Industry - Alinaitwe, Henry Mwanaki; Widén, Kristian; Mwakali, Jackson; Hansson, Bengt (Penerbit Universiti Sains Malaysia, 2007)
The construction industry has of recent been blamed for lack of innovation. Lack of innovation in the industry is believed to be responsible for the decreasing or stagnant levels of productivity in comparison with other industries. This paper reviews the major barriers and enablers to innovation in general. Propositions were made about the factors that affect innovation in the construction industry which were then formulated into a questionnaire. A survey was made on building contractors in Uganda, a developing country, targeting those with financial strength, large in size, and with high capacity to carry out big projects. The identified factors were then ranked and correlated. The level of training in science, engineering and technical education, and the level of research and development at the industry level are looked at as the greatest innovation enablers in building that will drive forward labour productivity. The size of the domestic market and the level of security are the worst innovation barriers that lead to low productivity in the building industry in Uganda. Contractors, policy makers and the government should address the identified factors in order to improve productivity.